Evaluation of antimicrobial activity and cytotoxicity of pegylated aminoglycosides. (May 2018) - Ahmadi, Zeba; Verma, Geeta; Jha, Diksha; Gautam, Hemant Kumar; Kumar, Pradeep
Here, in this study, we have investigated the antibacterial activity and cytotoxicity of pegylated aminoglycosides (gentamicin, kanamycin, and neomycin). The antibacterial activity of pegylated aminoglycosides, prepared in two different ratios (1:1 and 1:2, aminoglycoside:polyethylene glycol), was determined against some common pathogens, namely, Gram-positive ( Bacillus cereus, Staphylococcus aureus ) and Gram-negative ( Escherichia coli, Pseudomonas aeruginosa ), by zone of inhibition and minimum inhibitory concentration assays. The activity of pegylated aminoglycosides was found to be decreased as compared to their respective native aminoglycosides. Moreover, aminoglycoside:polyethylene glycol (1:1) derivatives showed much higher activity as compared to aminoglycoside:polyethylene glycol (1:2) derivatives, that is, an increase in the content of polyethylene glycol decreased the activity considerably. This decrease in antibacterial activity was found to be the most prominent in Gram-positive bacteria, S. aureus . On the other hand, pegylation significantly decreased the cytotoxicity as determined by hemolysis and MTT assays. These results advocate exploration of different types of crosslinkers consisting of a small degree of amphiphilicity, which could facilitate better interactions with the bacterial cell membranes and inhibit induction of bacterial resistance.